Adding capivasertib to fulvestrant in patients with hormone receptor-positive advanced breast cancer: a cost-effectiveness analysis - Yitian Lang; Qingqing Chai; Yan Lin; Bin Wu; Xiaoyan Liu (Frontiers in Pharmacology)
ObjectiveCapivasertib, a novel pan-AKT inhibitor, shows significant antitumor activity against hormone receptor-positive advanced breast cancer. However, its cost-effectiveness of this treatment remains uncertain. This study aimed to evaluate the cost-effectiveness of capivasertib plus fulvestrant versus fulvestrant alone for advanced breast cancer treatment from the perspectives of healthcare payers in the United States. Meanwhile, a experimental analysis from the perspective of China, incorporating specific assumptions, was also conducted in this study.MethodsA partitioned survival model was constructed to project the progression of breast cancer. Overall survival (OS) and progression-free survival (PFS) data were obtained from the CAPItello-291 trial and extrapolated for long-term survival estimates. Direct medical costs and utility data were gathered. The primary outcome measure was incremental cost-utility ratio (ICUR) to evaluate the cost-effectiveness of treatment regimen. One-way sensitivity analyses (OWSA) and probabilistic sensitivity analyses (PSA) were conducted to assess the robustness of the results.ResultsThe base-case analysis estimated the ICUR for capivasertib plus fulvestrant versus fulvestrant alone to be $709,647 per quality-adjusted life-year (QALY) in the US. OWSA revealed that the results were sensitive to hazard ratio of OS and the cost of capivasertib. PSA demonstrated that capivasertib plus fulvestrant exhibited a 0% probability of cost-effectiveness in the US.ConclusionOur finding suggests that, at its current price, capivasertib plus fulvestrant regimen is unlikely to be a cost-effective option compared to fulvestrant alone for HR-positive advanced breast cancer patients from the perspective of healthcare system in the US. For the experimental analysis based on specific assumptions from Chinese perspective, the therapy regimen was also found to lack cost-effectiveness.